Analisis Efisiensi Energi antara Lampu LED dan Lampu Konvensional (Studi kasus: Pada Hotel Cap Karoso) - Pramono, Lukito; Linawati, Linawati; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro; Vol 22 No 2 (2023): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2023.v22i02.P10, 2023)
LED lamps are an example of an efficiency method compared to conventional lamps because of their higher energy efficiency. In this research, a comparative analysis of electrical efficiency was carried out between LED lamps and conventional lamps. This research collected data from a number of lamps used in a comparative study of LED lamps and conventional lamps at the Cap Karoso Hotel and were tested under the same conditions. The types of LED lights used are recessed downlights, track lights, pendant lights and wall scones. While the types of conventional lamps used are incandescent, halogen, fluorescent and HID. Comparisons and calculations were made in terms of watt energy and electricity costs. Based on these parameters, it can be seen the energy produced and the costs required from both types of LED lamps and conventional lamps. Based on calculations and comparisons of the two types of lamps used, it is calculated that LED lamps can save energy and cost savings by 27%.